Proof-of-concept blockchain application for private marketplace - Tan, Wei Hsing (2019)
Technology advancement has improved rapidly throughout the years, and popular e-commerce marketplaces such as eBay and Amazon are able to provide more options to consumers than before. As a result, the potential of e-commerce to drive economic growth has gained much awareness. However, current e-commerce platforms are built on a centralized system and often run the risk of cybersecurity issues. On top of that, consumers are usually charged with extra fees through the usage of the financial services in the marketplace.